2021
DOI: 10.3390/reactions2020011
|View full text |Cite
|
Sign up to set email alerts
|

Fischer-Tropsch Synthesis: The Characterization and Testing of Pt-Co/SiO2 Catalysts Prepared with Alternative Cobalt Precursors

Abstract: Different low-cost cobalt precursors (acetate, chloride) and thermal treatments (air calcination/H2 reduction versus direct H2-activation) were investigated to alter the interaction between cobalt and silica. H2-activated catalysts prepared from cobalt chloride had large Co0 particles (XRD, chemisorption) formed by weak interactions between cobalt chloride and silica (temperature programmed reduction (TPR), TPR with mass spectrometry (TPR-MS), TPR with extended X-ray absorption fine structure (EXAFS) and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Through extensive experimental work on catalyst characterizations and catalyst testing, carbon nanofiber-supported cobalt catalyst stood out, which obtained 18.7% CO conversion and 94.7% C 5+ selectivity at 210 • C, 2.5 MPa, H 2 /CO = 2 and 5 NL/g-cat/h. A unique FTS study over Pt-Co/SiO 2 catalyst prepared with alternative cobalt precursors was reported by Professor Jacobs and his group of the University of Texas at San Aton Antonio [8]. Two low-cost cobalt catalyst precursors (acetate and chloride) were investigated along with varying thermal treatments.…”
mentioning
confidence: 99%
“…Through extensive experimental work on catalyst characterizations and catalyst testing, carbon nanofiber-supported cobalt catalyst stood out, which obtained 18.7% CO conversion and 94.7% C 5+ selectivity at 210 • C, 2.5 MPa, H 2 /CO = 2 and 5 NL/g-cat/h. A unique FTS study over Pt-Co/SiO 2 catalyst prepared with alternative cobalt precursors was reported by Professor Jacobs and his group of the University of Texas at San Aton Antonio [8]. Two low-cost cobalt catalyst precursors (acetate and chloride) were investigated along with varying thermal treatments.…”
mentioning
confidence: 99%